2015
DOI: 10.1021/acs.langmuir.5b01193
|View full text |Cite
|
Sign up to set email alerts
|

DFT-Derived Force Fields for Modeling Hydrocarbon Adsorption in MIL-47(V)

Abstract: Generic force fields such as UFF and DREIDING are widely used for predicting molecular adsorption and diffusion in metal-organic frameworks (MOFs), but the accuracy of these force fields is unclear. We describe a general framework for developing transferable force fields for modeling the adsorption of alkanes in a nonflexible MIL-47(V) MOF using periodic density functional theory (DFT) calculations. By calculating the interaction energies for a large number of energetically favorable adsorbate configurations u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 96 publications
(237 reference statements)
0
56
0
Order By: Relevance
“…It has been shown that generic force fields might not sample all relevant portions of the potential energy surface (PES). 65 We therefore extracted 100 configurations from snapshots of GCMC simulations (at 298 K and 1 bar) using all five force fields considered in this work, leading to a total set of 500 configurations. For the united-atom models, only the position of the carbon atom of methane can be extracted from the GCMC simulations: the orientation of the hydrogen atoms is in these cases determined randomly.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that generic force fields might not sample all relevant portions of the potential energy surface (PES). 65 We therefore extracted 100 configurations from snapshots of GCMC simulations (at 298 K and 1 bar) using all five force fields considered in this work, leading to a total set of 500 configurations. For the united-atom models, only the position of the carbon atom of methane can be extracted from the GCMC simulations: the orientation of the hydrogen atoms is in these cases determined randomly.…”
Section: Resultsmentioning
confidence: 99%
“…Several sets of LJ parameters for CH4 have been derived which are capable of predicting the behaviour of the bulk fluid in simulation, of which the TraPPE force field [37] is most commonly applied in studies of adsorption. Although a number of groups have derived framework LJ parameters for specific MOF-guest systems [38,39,40], the majority of studies make use of one of several generic force fields, of which the most common are UFF, DREIDING and OPLS-AA. Both UFF and DREIDING were developed and tested for their ability to predict crystal structures, bond lengths and bond angles for organic [25,41] and, in the case of UFF, organometallic molecular complexes [42], while OPLS-AA was developed to correctly reproduce properties of bulk organic liquids, such as the heat of vaporisation and liquid density [26,27].…”
Section: Force Field-based Calculationsmentioning
confidence: 99%
“…A pragmatic approach is the derivation of improved parameter sets from density-functional theory (DFT) calculations of adsorption energies at the CUS [41][42][43][44][47][48][49]. This strategy has yielded good results for alkanes, alkenes and alkynes in CUS-containing MOFs [19,43,44,[50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%